It's up to you: The need for self-directed learning for social work students on placement during COVID-19. (20th November 2021) - Zuchowski, Ines; Cleak, Helen; Croaker, Sandra; Davey, Jo-Bentley
Summary: COVID-19 in 2020 took social work programmes by surprise and for many students an e-placement was offered as the only alternative learning opportunity to complete their placement that year. In this article, we report on a mixed method study with data collected via an online survey with quantitative and qualitative questions exploring students' experiences in e-placements. Eighty-two students who had undertaken an e-placement responded to the survey that was sent to 1, 500 social work students enrolled in twenty-one Australian universities. The results summarise demographic data about the students and a description of the e-placements used, as well as qualitative themes about the students' experiences and recommendations about e-placements. Four themes were prominent in the qualitative data: 'opportunities for flexible learning but can be challenging', 'learning new skills but missing out on others', 'drive your own learning' and 'the need for structure, support and connection'. Most students reported that they learnt a range of social work skills, but this required them to take initiative to ensure that learning occurred. The implication for social work education underscores the importance of future proofing social work field education through examining the learning and providing proactive support and clear structures for alternatives to traditional placements. Abstract : Field education is an essential component of social work education. This research explored the experiences of Australian social work students who undertook e-placements in 2020 due to COVID-19. Eighty-two students responded to the survey. Findings highlight that while students appreciated the flexibility that e-placements provided, many struggled with aspects of online learning, and managing their own learning; that e-placement can offer new learning opportunity but that students can miss out on other social work learning, that students need to drive their own learning in e-placements, and that e-placements need to be supported with good structures, support and opportunities to connect to others. The article draws out implications for social work educators.